The association between hematological and inflammatory factors and stress fractures among female military recruits - Merkel, D.; Moran, D. S.; Yanovich, R.; Evans, R. K.; Finestone, A. S.; Constantini, N.; Israeli, E. (Medicine & Science in Sports & Exercise, 2008)
Background: With the growing number of females accepted for combat-related military duties in the Israeli Defense Forces, their special needs should be addressed. Previous studies on females in combat training have found a high prevalence of iron deficiency at recruitment as well as an increased rate of stress fractures (SF) and overuse injuries during training when compared with males. The aim of this study was to assess the correlation between hematological and inflammatory variables and SF occurrence among military recruits during basic training.